Pertimbangan Hakim Dalam Menjatuhkan Putusan Tindak Pidana Promosi Judi Online Melalui Media Sosial (Studi Putusan Nomor 498/Pid.Sus/2024/Pn Pdg) - Marisa Jemmy; Ad Azizi (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
The advancement of information technology in the digital era not only brings positive impacts but also creates opportunities for technology-based crimes (cybercrime), one of which is the promotion of online gambling through social media. Online gambling has rapidly developed due to massive promotions on digital platforms, thus requiring firm and effective law enforcement. This phenomenon is reflected in Decision Number 498/Pid.Sus/2024/PN Pdg, in which the defendant was proven to have promoted an online gambling site through clothing attributes worn in a video uploaded on the TikTok social media platform. The problems examined in this study are as follows: first, how were the judge’s considerations in deciding the criminal case of online gambling promotion through social media in Decision Number 498/Pid.Sus/2024/PN Pdg; and second, how was the evidentiary process applied in proving the criminal act of online gambling promotion through social media in the said decision. This research employs a normative legal research method with a descriptive nature, using library research as the data collection technique. The collected data were processed through editing and coding techniques and analyzed qualitatively. The results of the study indicate that the evidentiary system applied in Decision Number 498/Pid.Sus/2024/PN Pdg is the negative statutory proof system (negative wettelijk).The court found that the defendant was lawfully and convincingly proven to have committed the criminal act by fulfilling the elements of Article 45 paragraph (3) in conjunction with Article 27 paragraph (2) of Law Number 1 of 2024. The judge’s considerations were based on juridical, philosophical, and sociological aspects, including the defendant’s cooperative attitude and expression of remorse. However, the imposed sentence is considered disproportionate and insufficient to create a deterrent effect, as it is significantly lighter than the statutory provisions and the public prosecutor’s demands.